The Significance of the Increased Incidence of New Onset Seizures and Epilepsy After a COVID-19 Infection. (21st February 2023) - Bensken, Wyatt P.; O'Brien, Terence J.
Abstract : With over 600 million people infected worldwide, 1 including 95 million 2 in the United States as of September 2022, the lasting health consequences of the coronavirus disease 2019 (COVID-19) pandemic must be examined. Research has already highlighted several short-term and long-term neurologic consequences of COVID-19, including fatigue, headache, memory impairment, and other neurologic sequelae. 3, 4 With such a wide-reaching effect, there is a need to continue investigating the development of neurologic outcomes among individuals who were infected with COVID-19 to prepare the neurology workforce for a potential increase in patients and proactively identify opportunities to improve health outcomes.